Răspuns :
a - b = 705 si
a : b = 6 => a = 6b inlocuim ...
↓
6b - b = 705 ⇒ 5b = 705 adica: b = 705:5=141
↓
a = 6*141=846
Proba: a-b = 846 - 141 =705 (A)
a:b = 846:141 = 6 (A)
SAU...
a = |__|__|__|__|__|__| iar
b = |__|
=> a-b=|__|__|__|__|__|=705 deci |__|=705:5=141
R: a = 6*141=846
b= 1*141 =141
a : b = 6 => a = 6b inlocuim ...
↓
6b - b = 705 ⇒ 5b = 705 adica: b = 705:5=141
↓
a = 6*141=846
Proba: a-b = 846 - 141 =705 (A)
a:b = 846:141 = 6 (A)
SAU...
a = |__|__|__|__|__|__| iar
b = |__|
=> a-b=|__|__|__|__|__|=705 deci |__|=705:5=141
R: a = 6*141=846
b= 1*141 =141